Bevægelsesverber i polsk og dansk og ACCOMPLISHMENT-dilemmaet - Sobkowiak, Mikołaj (Folia Scandinavica Posnaniensia, 2009)
The article departs from Smith's (1997) claim that verb constellations constituted by a countable nominal, a verb of motion and a directional PP are ACCOMPLISHMENT constellations in line with 'The child built a house' or 'He wrote a novel'. A series of morphological and syntactic tests are applied to perfective and imperfective ACCOMPLISHMENTS of directed motion in Polish and Danish (biec / at løbe, iść / at gå, lecieć / at flyve og jechać / at køre + directional adverbials). This illustrates that the verb constellations of interest do not always show the features of canonical ACCOMPLISHMENTS that do not refer to motion as such.